Acute Arterial Thrombosis after Covered Stent Exclusion of Bleeding Mycotic Pseudoaneurysm: Treatment Using Catheter-Directed Thrombolysis - Sarah Palestrant; M. Grace Knuttinen; Ron C. Gaba; James T. Bui; Charles A. Owens (International Journal of Vascular Medicine)
Conventional absolute contraindications to catheter-directed thrombolysis include active or recent hemorrhage and the presence of local vascular infection, both of which increase the risk of procedure-related complications such as bleeding and systemic sepsis. For this reason, lytic therapy of arterial thromboembolism under these circumstances is generally precluded. Herein, we describe a unique case of safe catheter-directed lysis of an acutely thrombosed iliac artery following covered stent placement for treatment of an actively bleeding infected pseudoaneurysm. Our management approach is discussed.